The Epic of Imam Ali (peace be upon him) by Abdul-Masih al-Antaki - A Narrative Study (Journal of the College of Basic Education, 2026)
The interweaving of narrative elements within a poetic text is an important method for constructing any creative text. Its importance is evident in several aspects, including the fact that it generates complex creative texts that blend different genres, a variety of expressive styles, and a variety of techniques used in creating texts. Furthermore, it provides greater freedom and space for the creator to express their feelings and emotions without being bound by a single format. Furthermore, it demonstrates the author's creative potential.The epic poem "Imam Ali (peace be upon him)" by Abdul-Masih al-Antaki expressed the sincerity of his feelings and emotions toward the Commander of the Faithful (peace be upon him). This epic demonstrated the sincerity of emotion and admiration of its author, who attempted to translate this sincerity and emotion through his composition of the epic, which chronicles the life of the Commander of the Faithful, an immortal figure throughout history.